Extracellular Vesicles as Potential Prognostic Markers of Lymphatic Dysfunction - Milasan, Andreea; Farhat, Maya; Martel, Catherine (Frontiers in Physiology, 2020)
Despite significant efforts made to treat cardiovascular disease (CVD), more than half of cardiovascular events still occur in asymptomatic subjects devoid of traditional risk factors. These observations underscore the need for the identification of new biomarkers for the prevention of atherosclerosis, the main underlying cause of CVD. Extracellular vesicles (EVs) and lymphatic vessel function are emerging targets in this context. EVs are small vesicles released by cells upon activation or death that are present in several biological tissues and fluids, including blood and lymph. They interact with surrounding cells to transfer their cargo, and the complexity of their biological content makes these EVs potential key players in several chronic inflammatory settings. Many studies focused on the interaction of EVs with the most well-known players of atherosclerosis such as the vascular endothelium, smooth muscle cells and monocytes. However, the fate of EVs within the lymphatic network, a crucial route in the mobilization of cholesterol out the artery wall, is not known. In this review, we aim to bring forward evidence that EVs could be at the interplay between lymphatic function and atherosclerosis by summarizing the recent findings on the characterization of EVs in this setting.